A Study of Students’ Science Process Skills at A National–Plus Middle School in Tarakan - Listiani Listiani; Arief Ertha Kusuma (Berkala Ilmiah Pendidikan Fisika, 2024)
Process science skills are essential for students to understand how the world works. This performance can be measured by exploring students' capacity for scientific knowledge development. The study investigated the science process skills of high school students at one of the National Plus Junior High Schools in Tarakan. The science process skills test was conducted by giving multiple-choice questions to 74 students referring to four indicators: interpreting, graphing, inferring, and explaining. Students answered ten questions representing the five indicators of science process skills under study. The results showed that, in general, students' science process skills in the National Plus Junior High Schools were relatively low. 77.3% of students were in the low category, 4.8% were in the medium category, and 17.9% had high science process skills. The interpreting indicators are at a moderate level (64%), while the other three skills are low, with percentages of 47%, 44%, and 22%, respectively. The low percentage of these four indicators indicates that science lessons need to be optimized by paying attention to and integrating science process skills in student activities during learning. Science teachers should be trained in integrating science process skills into learning. Therefore, developing and applying a learning model that can train science process skills comprehensively and can be implemented optimally is necessary.